COVID-19 vaccine acceptance among high-risk populations in Uganda - Bongomin, Felix; Olum, Ronald; Andia-Biraro, Irene; Nakwagala, Frederick Nelson; Hudow Hassan, Khalid; Nassozi, Dianah Rhoda; Kaddumukasa, Mark; Byakika-Kibwika, Pauline; Kiguli, Sarah; Kirenga, Bruce J. (Therapeutic Advances in Infectious Disease, 2021)
Immunization is an important strategy for controlling the COVID-19 pandemic. COVID-19 vaccination was recently launched in Uganda, with prioritization to healthcare workers and high-risk individuals. In this study, we aimed to determine the acceptability of COVID-19 vaccine among persons at high risk of COVID-19 morbidity and mortality in Uganda. Methods: Between 29 March and 14 April 2021, we conducted a cross-sectional survey consecutively recruiting persons at high risk of severe COVID-19 (diabetes mellitus, HIV and cardiovascular disease) attending Kiruddu National Referral Hospital outpatient clinics. A trained research nurse administered a semi-structured questionnaire assessing demographics, COVID-19 vaccine related attitudes and acceptability. Descriptive statistics, bivariate and multivariable analyses were performed using STATA 16.
Keywords: COVID-19; High-risk population; Uganda; Vaccines